Розвиток сфери виробничого обслуговування сільського господарства Волинської області в 1965-1985 рр. - Гусак, Дарина; Husak, Daryna (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті розглянуто проблемні питання розвитку сфери виробничого обслуговування сільського господар-ства Волинської області у 1965−1985 рр., а саме: система заготівлі продукції, меліорація, ветеринарія, захист рослин.

The problem tasks in the development of agriculture production service in Volyn region in 1965–1985 are analysed in the article. The system of products provision, irrigation system, plant protection and veterinary were important compo-nents. Production power increasing, manual processes mechanization, technological processes improving, qualified human resources training, new agricultural objects building were main tasks in the development of agriculture. Based on materials of State archive of Volyn region and statistics the author reproduces objective state of above-mentioned components. The theme is actual because it is possible to study other parts of agricultural production service, such as: communication, transport, logistical equipment.
The Development of Agriculture Production Service Sphere in Volyn Region in 1965–1985
Keywords: сільське господарство; заготівля продукції; меліорація; ветеринарія; захист рослин; agriculture; products provision; reclamation; veterinary; plant protection